Can we reduce the surgical site infection rate in cesarean sections using a chlorhexidine-based antisepsis protocol?. (November 2013) - Amer-Alshiek, Jonia; Alshiek, Tahani; Almog, Benny; Lessing, Joseph B.; Satel, Abed; Many, Ariel; Levin, Ishai
Abstract Objective: To determine whether chlorhexidine-based antisepsis reduces the rate of surgical site infections (SSIs) in elective and non-elective cesarean sections (CS) compared with povidone-iodine protocol. Methods: This was a retrospective study. Women undergoing elective and non-elective CS during two periods of time who were treated with two different antisepsis protocols were included. The protocols for antisepsis were povidone-iodine 10% scrub followed by 10% povidone-iodine in 65% alcohol (n = 163) and chlorhexidine 2% followed by 70% alcohol (n = 163). The rate of SSIs and the risk factors for their occurrence were calculated and compared between the two groups. Results: Antisepsis with chlorhexidine and alcohol was associated with a lower rate of SSIs, 10.43% versus 3.07% with povidone-iodine (p = 0.08). The two groups of patients were similar in baseline characteristics. Risk factors associated with SSIs were body mass index, urgent CS, and the use of the povidone-iodine protocol. Conclusions: Antisepsis with Chlorhexidine-based regimen was associated with a significant reduction in the rate of SSIs compared to povidone-iodine antisepsis in women undergoing elective and non-elective CS. This is of extreme clinical importance, as a change in antisepsis protocol can significantly reduce the morbidity and healthcare costs regarding cesarean sections.